Some theorems in existence and oneness of a system of integral - nonlinear differential equations - Raed Butrus; Mirna Azeez (College of Education for Pure Sciences, 2006)
In this paper we study the existence and uniqueness solution for system of nonlinear integro-differential equations by usingRiemann integral. For this purpose, the study depends upon(Picard approximation Method) and (Banach fixed point theorem).